PERAN UNICEF DALAM MEMBANTU MEMAJUKAN PEMENUHAN HAK ANAK ATAS PENDIDIKAN DI NIGERIA - Melia Dwiyani, Made Ayu; Rainy Priadarsini, Ni Wayan; Prameswari, A.A.Ayu Intan (Program Studi Hubungan Internasional FISIP Universitas Udayana, 2015)
ABSTRAK Education is one of the rights that are required for children. Nigeria is one country with the state of their children's education are still below the average standards are set by the government, particularly in school education. International organizations such as UNICEF to focus on children and women have an international program to help advance the fulfillment of child rights. This study aims to describe the role of UNICEF in an effort to help promote the realization of children's right to education in Nigeria. This study will be discussed using the theory and concept of the role of international organizations, development intervention, education, and the rights of children by the time span from 2002 to 2007 which is a vulnerable time education program in Nigeria. Keywords: UNICEF, Children, Education, Nigeria